Rapid on-resin N-formylation of peptides as one-pot reaction - Kokollari, Agon; Werner, Marius; Lindner, Christina; Pham, Truc Lam; Thomas, Franziska (ChemBioChem, 2023)
N-formylation is a common pre- and post-translational modification of the N-terminus or the lysine side chain of peptides and proteins that plays a role in the initiation of immune responses, gene expression, or epigenetics. Despite its high biological relevance, protocols for the chemical N-formylation of synthetic peptides are scarce. The few available methods are elaborate in their execution and the yields are highly sequence-dependent. We present a rapid, easy-to-use one-pot procedure that runs at room temperature and can be used to formylate protected peptides at both the N-terminus and the lysine side chain on the resin in near-quantitative yields. Only insensitive, storage-stable standard chemicals - formic acid, acetic anhydride, pyridine and DMF - are used. Formylation works for both short and long peptides of up to 34 amino acids and over the spectrum of canonical amino acids.